Metatextual Awareness, reading comprehension and story summary – possible relations in a psycholinguistic perspective - Lopes, Marília Marques (2016)
Even before formal education, children have a long term for developing their abilities of reading and writing, and these abilities relate to both reading comprehension and awareness of texts, whatever they are. This Metatextual Awareness, according to Jean-Émile Gombert (1992), comprises coherence, cohesion and text structure, and is a factor that can determine a good comprehension, as well as summary writing. The thesis this article is about employed Gombert’s theoretical framework on that subject, and dealt with correlations among metatextual awareness, reading comprehension and summary writing of narratives by 5th and 6th grade students in three public schools in Porto Alegre. To check these correlations, we applied simple choice tests to evaluate metatextual awareness and reading comprehension, and also a test of summary writing through a reference framework comprising categories like main events, writing autonomy and narrative structure. The results of these three aspects were related and we found that for summarizing a story the most important is the subject’s metatextual ability, or his attention to source text. At the same time, this metatextual awareness is also relevant to text comprehension as it is a kind of frame that guides him in understanding a story.